Effect of Temperature on Methane Adsorption in Shale Gas Reservoirs - Zou, J.; Rezaee, M. Reza; Liu, K. (American Chemical Society, 2017)
Methane adsorption isotherms on shale were investigated at 25, 45, 60, and 80 °C with pressure up to 7 MPa (1015 psi). A total of six shale samples with low total organic carbon (TOC) from the Perth Basin and Canning Basin (Western Australia) were studied to quantify the effect of temperature on methane adsorption in shale gas reservoirs. The pore structure of the shale samples was measured using low-pressure nitrogen and carbon dioxide adsorption. At low temperature (25 °C), the methane adsorption isotherms show a general increase of methane adsorption with the TOC. However, the trend is not in line with methane adsorption at high temperature (80 °C). At 80 °C, sample AC-2 with 0.64% TOC has a larger maximum methane adsorption capacity than sample AC-4 with 1.03% TOC, indicating that the effects of temperature on methane adsorption for different shale samples are different. As the temperature increases, the decrease rate of methane adsorption on low TOC samples is smaller than that on the samples with a high TOC content. All the experimental methane adsorption isotherms fit well with the Langmuir equation. The Langmuir volumes of samples AC-2 (0.64% TOC), AC-4 (1.03% TOC), and AC-5 (0.23% TOC) are very close to each other at high temperature (80 °C). The thermodynamic parameters of methane adsorption on shale samples were determined. For the studied shale samples, the heat of adsorption and the standard entropy range from 4.5 to 14.5 kJ/mol and from 42.0 to 74.7 J mol–1 K–1, respectively.